JOB STRESS AND JOB SATISFACTION AMONG EDUCATORS IMPACT ON EDUCATIONAL INSTITUTION PERFORMANCE - Mohamad Zaki Hardi, Lalu; Wiresentana, Lalu; Khusniyah, Nurul Lailatul (Indonesian Journal of Educational Development (IJED), 2025)
This study examines the complex relationship between job stress, job satisfaction, and their combined effects on organizational performance, utilizing a qualitative approach through a Systematic Literature Review. The analysis incorporates literature from various databases, including Dimensions, Scopus, Google Scholar, and DOAJ, spanning publications from 2015 to 2024. The findings demonstrate that job stress significantly influences key organizational outcomes, such as turnover intentions, job satisfaction, and both individual and team performance. Job dissatisfaction and low organizational commitment are identified as mediating factors that exacerbate the adverse effects of stress on turnover intentions. In contrast, role clarity is highlighted as a vital element in reducing the detrimental impact of stress on job performance, contributing to greater stability and efficiency. The review underscores the dynamic interactions between stress and its consequences, advocating for the implementation of comprehensive organizational strategies to manage stress effectively. These strategies should focus on fostering organizational justice, clarifying employee roles, and strengthening support systems to enhance job satisfaction and productivity. By providing evidence-based insights, this research contributes to a deeper understanding of workplace challenges and emphasizes the importance of targeted interventions to promote employee well-being and organizational success, ultimately supporting sustainable development.